2020
DOI: 10.4081/ejh.2020.3131
|View full text |Cite
|
Sign up to set email alerts
|

Visnagin ameliorates myocardial ischemia/reperfusion injury through the promotion of autophagy and the inhibition of apoptosis

Abstract: Visnagin is a furanochromone and one of the main compounds of Ammi visnaga L. that had been used to treat nephrolithiasis in Ancient Egypt. Nowadays, visnagin was widely used to treat angina pectoris, urolithiasis and hypertriglyceridemia. The potential mechanisms of visnagin involved in inflammation and cardiovascular disease were also identified. But the protective effect of visnagin on myocardial ischemia/reperfusion injury has not been confirmed. Our aim was, for the first time, to investigate the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Many pharmacologic interventions (e.g., visnagin, alliin, resveratrol, and hydrogen-rich saline) have been found to protect the heart from IRI by enhancing autophagy flux. 40 , 41 , 42 , 43 Some medications (e.g., calreticulin, geniposide, berberine, and tetramethylprazine) have been found to protect the heart by inhibiting autophagy or improving impaired autophagy flux. 28 , 44 , 45 , 46 In addition, some non-coding RNAs targeting autophagy have also been shown to play important roles in MIRI.…”
Section: Autophagy and Myocardial Ischemia/reperfusion (I/r)mentioning
confidence: 99%
“…Many pharmacologic interventions (e.g., visnagin, alliin, resveratrol, and hydrogen-rich saline) have been found to protect the heart from IRI by enhancing autophagy flux. 40 , 41 , 42 , 43 Some medications (e.g., calreticulin, geniposide, berberine, and tetramethylprazine) have been found to protect the heart by inhibiting autophagy or improving impaired autophagy flux. 28 , 44 , 45 , 46 In addition, some non-coding RNAs targeting autophagy have also been shown to play important roles in MIRI.…”
Section: Autophagy and Myocardial Ischemia/reperfusion (I/r)mentioning
confidence: 99%
“…In this study, ISO induced an increase in the cardiac damage biomarkers cTnT and cTnI, which was significantly suppressed by SGI treatment. LV systolic and diastolic dysfunction during MI has emerged as an important indicator of cardiac function ( Zhang et al, 2016 ; Fu et al, 2020 ). In echocardiography, EF(%) and FS(%) values were decreased and LV systolic dysfunction was observed in the MI rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of acute myocardial ischemia‐reperfusion injury, it was found that the autophagy level of rats treated with CoQ10 was improved, the antioxidant capacity was enhanced, and the cardiac function was improved, suggesting that CoQ10 may alleviate acute myocardial ischemia‐reperfusion injury through antioxidant and autophagy pathways 153 . Visnagin has been proved to be closely related to the occurrence and development of cardiovascular diseases 154 . It can alleviate myocardial ischemia‐reperfusion injury and has a potential protective effect on cardiac function.…”
Section: The Link Between Autophagy and Ferroptosis In Cardiovascular...mentioning
confidence: 99%